2022
DOI: 10.1097/sap.0000000000003191
|View full text |Cite
|
Sign up to set email alerts
|

A Social Media Analysis of Wellness Culture in Plastic Surgery Residency

Abstract: Background Burnout, “a psychological syndrome of emotional exhaustion, depersonalization, and reduced personal accomplishment”, afflicts approximately one third of plastic surgery attending surgeons and residents. Burnout can be detrimental to resident training and patient outcomes. Therefore, cultivating wellness during residency is essential. In fact, the Accreditation Council for Graduate Medical Education requires residency programs to create learning and working environments that optimize facu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Our study sought to identify posts including many forms of diversity. Additionally, plastic surgery literature is congruent in our results showing wellness is in the minority posted, despite the recent emphasis on combating burnout in medicine [ 30 ]. Ultimately, programs should consider including content that represents their program’s unique aspects and core values.…”
Section: Discussionsupporting
confidence: 65%
“…Our study sought to identify posts including many forms of diversity. Additionally, plastic surgery literature is congruent in our results showing wellness is in the minority posted, despite the recent emphasis on combating burnout in medicine [ 30 ]. Ultimately, programs should consider including content that represents their program’s unique aspects and core values.…”
Section: Discussionsupporting
confidence: 65%
“…Instagram accounts have the ability to candidly show residents’ day-to-day routine at work, resident life outside the hospital, work-life balance, educational highlights, and other aspects of program culture and wellness that would not traditionally be available to applicants. 4 All of these insights provided by social media may influence program rank lists. 5 Social media accounts can also display more widely available information in a novel manner through faculty highlights, alumni features, and publication spotlights.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, one study found that 93% of PRS residency programs had an active Instagram account. 9 SoMe has played a growing role in the residency match process, a trend accelerated by the COVID-19 pandemic. 10 Although SoMe is not a required component of the match process, the unofficial role it plays is crucial.…”
Section: Introductionmentioning
confidence: 99%